(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article provides information about noise and vibration that occurs in industrial enterprises. By its physical nature, noise is a mechanical oscillatory motion. The main physical parameters of noise are: sound pressure, sound intensity, frequency response of sound. Noise and vibration cause noise and vibration diseases, and this is their complex effect on the central nervous system, motor system and cardiovascular activity of a person. The article provides a description of a portable sound level meter and the results of calculations from fans and draft equipment.